MANAGEMENT CAPABILITY TO PRODUCE QUALITY EARNING - Edi Edi; Santi Yopie (Jurnal Reviu Akuntansi dan Keuangan, 2019)
This research aims at analyze the effects of management ability to earning quality that is measured by restatement, earning persistence, and accrual quality. The objective of this research is to examine how far the capabilities of firm’s management can make earning for the firm to become more qualified                 The research populations were taking from the non-financial reports of companies listed in Indonesia Stock Exchange in the period 2008 until 2016. The sample used for this research are 248 firm or 1.240 observation data which was using purposive sampling method.                  This research uses panel regression method to analyze the effect of independent variables on the dependent variable. The observation data are analyzed and processed using Statistical Package for the Social Sciences (SPSS) and Eviews 7th version.            The result indicates that management ability, independent directors and the total number of directors significant to earning quality that is measured by earning restatement, earning persistence and accrual quality in Indonesia Stock Exchange.